Antibodies IgA, IgE, IgM, and IgG Reactivities Against Two Species of Anisakis in Three Cases of Anisakis Allergy - Makoto Kondo; Koji Habe; Keiichi Yamanaka (Clinical Case Reports, 2025)
ABSTRACT The current state of research on Anisakis allergy remains insufficiently understood. It is believed that the interaction between the complex combination of Anisakis protein components and the immune regulatory mechanisms of the human body plays a role. However, many studies have focused on a single immunoglobulin. Therefore, we examined the response of IgA, IgE, IgM, and IgG to the constituent proteins of the two Anisakis species. The subjects included a patient who developed Anisakis‐induced urticaria (Case 1), who had a history of urticaria (Case 2), and who had experienced gastrointestinal symptoms caused by Anisakis in the past (Case 3). These cases were comprehensively evaluated using Western blotting analysis. This study found distinct immune response differences between Anisakis simplex (A. simplex) and Anisakis pegreffii (A. pegreffii) in three patient cases. All patients showed antigen–antibody reactions to both species, with stronger responses to A. simplex. IgE and IgA responses were more prominent compared to those with IgG and IgM. In Case 1, recurring urticaria corresponded with elevated IgE and IgA levels, with IgE reactions observed at several molecular weights. Intense IgM reactions appeared around 20 kDa for both species. Case 2, with resolved urticaria, showed weaker immune responses. Case 3, despite no intestinal symptoms, displayed reactions similar to Case 2, particularly for IgA and IgM. Even in patients without a long‐standing Anisakis allergy, all immunoglobulins respond to certain Anisakis components. Once developed, the allergy may recur unexpectedly.